The Effectiveness of Youcut and Canva Application Training for Making Learning Media in Early Childhood Education in the City of Bandung - ., Nurul Afrianti; ., Enoh; ., Masnipal; Sobarna, Ayi; Dudi, Asep; Marwah, Hasna; Afifah, Hasna (KnE Social Sciences, 2023)
The results of observations and interviews with teachers, school principals, and the Head of Early Childhood Teacher Association (HIMPAUDI), revealed that the problem of the lack of knowledge and skills of early childhood teachers in making learning media caused the implementation of learning to be still conventional, especially during this pandemic, mastery of ICT-based learning media (for example making learning videos) should be more qualified. The purpose of implementing community service is to improve the ability of childhood teachers in Bandung Wetan subdistrict, Bandung City in making ICT-based learning media. Community service provides an easy solution and is in accordance with the development of the era and the current digital era in making learning media. The low understanding of using technology can be seen from the few institutions that make learning media during distance learning activities. Specific targets to be achieved include: a) teachers understanding on how to make ICT-based learning media routinely and regularly; b) teachers understanding the steps in making ICT-based learning media; c) teachers being able to take advantage of ICT in hardware and mobile phones in facilitating the manufacturing of learning media. The training methods taken include, firstly, providing information about knowledge and technological developments, especially computers and cell phones. Second, the introduction of applications to create learning media in this case learning videos. Third, the introduction and development of applications for learning media. Fourth, the simulation of making learning media using applications. Fifth, application implementation information. The results of the training based on statistical calculations obtained a p-value of 0.006. With a 95% confidence level, because the p-value is less than 0.05, this means that there was a significant difference between the participants∧ abilities before and after the training. Keywords: early childhood, teacher, training, ICT-based learning media